2012
DOI: 10.1111/j.1365-3164.2012.01046.x
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus pseudintermedius in the dog: taxonomy, diagnostics, ecology, epidemiology and pathogenicity

Abstract: The dog is the natural host of Staphylococcus pseudintermedius. Many research efforts are currently being undertaken to expand our knowledge and understanding of this important canine commensal and opportunistic pathogen. The objective of this review is to summarize the current knowledge of the species, including the latest research outcomes, with emphasis on taxonomy, diagnostics, ecology, epidemiology and pathogenicity. Despite the important taxonomic changes that have occurred over the past few years, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
335
0
26

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 312 publications
(381 citation statements)
references
References 140 publications
(236 reference statements)
20
335
0
26
Order By: Relevance
“…However, Devriese et al 2005 using molecular characterization in samples from canine, fox, and pigeon, found three different species among those known as S. intermedius. Those three species, S. pseudintermedius, S. intermedius, and S. delphini, compose the S. intermedius Group (SIG) (Devriese et al 2005, Bannoehr & Guardabassi 2012, Miller et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…However, Devriese et al 2005 using molecular characterization in samples from canine, fox, and pigeon, found three different species among those known as S. intermedius. Those three species, S. pseudintermedius, S. intermedius, and S. delphini, compose the S. intermedius Group (SIG) (Devriese et al 2005, Bannoehr & Guardabassi 2012, Miller et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…It is the major cause of canine skin and ear infections [2,3]. Furthermore, human infections are sporadically reported [4,5], suggesting that, although it is estimated to be low, there is a threat of zoonotic disease.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, en el año 2005 este género fue reclasificado taxonómicamente, considerándose actualmente como S. pseudintermedius a la gran mayoría de los aislados de perros y gatos y algunos de equinos 6 . Las pruebas fenotípicas no son de gran ayuda para diferenciar S. intermedius de S. pseudintermedius 7 , por lo que se prefiere considerar a los aislados de S. intermedius como pertenecientes al "grupo de S. intermedius" (SIG, por sus siglas en inglés). La virulencia de estas especies se asocia a la producción de coagulasa, por lo que los aislados capaces de producirla son clasificados como "Staphylococcus coagulasa positiva" (SCP).…”
Section: Introductionunclassified